Beta-palmitate – a natural component of human milk in supplemental milk formulas. Issue 1 (December 2015) - Havlicekova, Zuzana; Jesenak, Milos; Banovcin, Peter; Kuchta, Milan
Abstract The composition and function of human milk is unique and gives a basis for the development of modern artificial milk formulas that can provide an appropriate substitute for non-breastfed infants. Although human milk is not fully substitutable, modern milk formulas are attempting to mimic human milk and partially substitute its complex biological positive effects on infants. Besides the immunomodulatory factors from human milk, research has been focused on the composition and structure of human milk fat with a high content of β-palmitic acid (sn-2 palmitic acid, β-palmitate). According to the available studies, increasing the content of β-palmitate added to milk formulas promotes several beneficial physiological functions. β-palmitate positively influences fatty acid metabolism, increases calcium absorption, improves bone matrix quality and the stool consistency, and has a positive effect on the development of the intestinal microbiome.